Autophagy in intestinal fibrosis: relevance in inflammatory bowel disease - Macias-Ceja, Dulce C.; Barrachina, María D.; Ortiz-Masià, Dolores (Frontiers in Pharmacology, 2023)
Chronic inflammation is often associated with fibrotic disorders in which an excessive deposition of extracellular matrix is a hallmark. Long-term fibrosis starts with tissue hypofunction and finally ends in organ failure. Intestinal fibrosis is not an exception, and it is a frequent complication of inflammatory bowel disease (IBD). Several studies have confirmed the link between deregulated autophagy and fibrosis and the presence of common prognostic markers; indeed, both up- and downregulation of autophagy are presumed to be implicated in the progression of fibrosis. A better knowledge of the role of autophagy in fibrosis may lead to it becoming a potential target of antifibrotic therapy. In this review we explore novel advances in the field that highlight the relevance of autophagy in fibrosis, and give special focus to fibrosis in IBD patients.